DEVELOPMENT OF OPEN-ENDED PROBLEM BASED-STUDENT WORKSHEETS TO IMPROVE STUDENTS' CREATIVE THINKING ABILITY - Dina Prasetyowati; Kartinah Kartinah; Sony Junaedi (Proceeding International Conference on Digital Education and Social Science, 2022)
This study aims to develop open-ended problem-based Student Worksheets to improve creative thinking skills in a valid mathematics course for junior high school and implementation of field trials using Student Worksheets that are developed effectively with the output of open ended problem-based Student Worksheets. The development procedure uses the model developed by Borg and Gall which consists of 10 stages. However, this study only reached the 5th stage, namely (1) Collecting Research and information, (2) Planning, (3) Developing a preliminary form of product, (4) Testing the preliminary field, and (5) Revising the main product. Student Worksheet (SW) that has been developed has gone through a validation process determined by experts or experts in their fields. The average score given by the validator is 4.60 out of a maximum score of 5. Learning by using an open ended-based Student Worksheet to improve creative thinking skills in mathematics courses for junior high school generates effective learning based on (1) the average grade of class students The experimental class reached more than the KKM, namely 85.79 so that the experimental class was completed classically. (2) the results of student achievement in the experimental class are better than in the control class. The values ​​obtained were 85.79 for the experimental class and 66.93 for the control class. Based on the results of the valid and effective learning tools mentioned above, the development of learning tools achieves the desired results, which are feasible to use.